Childhood sexual abuse and the development of recurrent major depression in Chinese women. - Jing Chen (Public Library of Science (PLoS), 2014)
Background Our prior study in Han Chinese women has shown that women with a history of childhood sexual abuse (CSA) are at increased risk for developing major depression (MD). Would this relationship be found in our whole data set? Method Three levels of CSA (non-genital, genital, and intercourse) were assessed by self-report in two groups of Han Chinese women: 6017 clinically ascertained with recurrent MD and 5983 matched controls. Diagnostic and other risk factor information was assessed at personal interview. Odds ratios (ORs) were calculated by logistic regression. Results We confirmed earlier results by replicating prior analyses in 3,950 new recurrent MD cases. There were no significant differences between the two data sets. Any form of CSA was significantly associated with recurrent MD (OR 4.06, 95% confidence interval (CI) [3.19-5.24]). This association strengthened with increasing CSA severity: non-genital (OR 2.21, 95% CI 1.58-3.15), genital (OR 5.24, 95% CI 3.52-8.15) and intercourse (OR 10.65, 95% CI 5.56-23.71). Among the depressed women, those with CSA had an earlier age of onset, longer depressive episodes. Recurrent MD patients those with CSA had an increased risk for dysthymia (OR 1.60, 95%CI 1.11-2.27) and phobia (OR 1.41, 95%CI 1.09-1.80). Any form of CSA was significantly associated with suicidal ideation or attempt (OR 1.50, 95% CI 1.20-1.89) and feelings of worthlessness or guilt (OR 1.41, 95% CI 1.02-2.02). Intercourse (OR 3.47, 95%CI 1.66-8.22), use of force and threats (OR 1.95, 95%CI 1.05-3.82) and how strongly the victims were affected at the time (OR 1.39, 95%CI 1.20-1.64) were significantly associated with recurrent MD. Conclusions In Chinese women CSA is strongly associated with recurrent MD and this association increases with greater severity of CSA. Depressed women with CSA have some specific clinical traits. Some features of CSA were associated with greater likelihood of developing recurrent MD.